Strategies for Targeting Neural Circuits: How to Manipulate Neurons Using Virus Vehicles - Hui, Yuqing; Zheng, Xuefeng; Zhang, Huijie; Li, Fang; Yu, Guangyin; Li, Jiong; Zhang, Jifeng; Gong, Xiaobing; Guo, Guoqing (Frontiers in Neural Circuits, 2022)
Viral strategies are the leading methods for mapping neural circuits. Viral vehicles combined with genetic tools provide the possibility to visualize entire functional neural networks and monitor and manipulate neural circuit functions by high-resolution cell type- and projection-specific targeting. Optogenetics and chemogenetics drive brain research forward by exploring causal relationships among different brain regions. Viral strategies offer a fresh perspective for the analysis of the structure-function relationship of the neural circuitry. In this review, we summarize current and emerging viral strategies for targeting neural circuits and focus on adeno-associated virus (AAV) vectors.